BIOMARKERS OF INFLAMMATORY ASTHMA PHENOTYPES - Plavšić, Aleksandra (Medicinski podmladak, 2024)
Asthma is characterized by heterogeneity and variability in pathophysiologic mechanisms, clinical presentation, therapy response and exacerbations. Asthma is defined as a syndrome that is compromised by different endotypes and phenotypes. A phenotype evolves all asthma features and characteristics, and by applying personalized medicine concept, should be determined in every single asthma patient with personalized therapy approach. Based on induced sputum analysis, that corresponds with airway inflammation, there are 4 different inflammatory phenotypes: eosinophilic, neutrophilic, mixed and paucigranulocytic. There are two phenotypes based on key molecular asthma attributes: Type T2 (T2) and non Type 2 (non-T2). Biomarkers have very big and important role in defining phenotype, and they should be easily accessible, they should indicate pathophysiological process and clinical response to therapy. Currently, there are no precise established T2 phenotype biomarkers, however, eosinophils, fraction of exhaled nitric oxide (FeNO), IgE have the biggest potential of T2 phenotype determination and have been largely investigated; while non T2 biomarkers are not described. Phenotypes may overlap and change over the time which makes determining biomarkers, as a complete indicator of all phenotypes features, very difficult and demanding. At the same time, biomarkers evaluation present great challenge in future research, giving high asthma prevalence.
Keywords: phenotype; biomarkers; T2 asthma; non-T2 asthma